Natural variant of the Helicobacter pylori CagA oncoprotein that lost the ability to interact with PAR1 - Hashi, Kana (BlackWell Publishing Ltd, 2014)
Helicobacter pylori strains carrying the cagA gene are associated with severe disease outcomes, most notably gastric cancer. CagA protein is delivered into gastric epithelial cells by a type IV secretion system. The translocated CagA undergoes tyrosine phosphorylation at the C-terminal EPIYA motifs by host cell kinases. Tyrosine-phosphorylated CagA acquires the ability to interact with and activate SHP2, thereby activating mitogenic signaling and inducing cell morphological transformation (hummingbird phenotype). CagA also interacts with PAR1b via the CM sequence, resulting in induction of junctional and polarity defects. Furthermore, CagA-PAR1b interaction stabilizes the CagA-SHP2 complex. Because transgenic mice systemically expressing CagA develop gastrointestinal and hematological malignancies, CagA is recognized as a bacterium-derived oncoprotein. Interestingly, the C-terminal region of CagA displays a large diversity among H. pylori strains, which influences the ability of CagA to bind to SHP2 and PAR1b. In the present study, we investigated the biological activity of v225d CagA, an Amerindian CagA of H. pylori isolated from a Venezuelan Piaroa Amerindian subject, because the variant CagA does not possess a canonical CM sequence. We found that v225d CagA interacts with SHP2 but not PAR1b. Furthermore, SHP2-binding activity of v225d CagA was much lower than that of CagA of H. pylori isolated from Western countries (Western CagA). v225d CagA also displayed a reduced ability to induce the hummingbird phenotype than that of Western CagA. Given that perturbation of PAR1b and SHP2 by CagA underlies the oncogenic potential of CagA, the v225d strain is considered to be less oncogenic than other well-studied cagA-positive H. pylori strains.